Resource allocation scheme for D2D communication in mmWave 5G networks - Bing YI; Yongli CHEN; Ruixue ZHAO (Dianxin kexue)
Since the combination of device-to-device (D2D) and mmWave technology can meet the needs of large-capacity, resource allocation was considered for D2D users in an outdoor millimeter wave scenario. The optimal objective was maximize to the total system throughput. Firstly, the admission set of each D2D user was selected by a linear correlation method. Then, power control was performed on the D2D user to select the optimal transmit power. Finally, a multi-phase matching algorithm based on bipartite graph was proposed to allocate resources for D2D users, and the allocation result was obtained by using multiple KM algorithms. The simulation results show that the proposed algorithm is superior to the comparison algorithm, which effectively improves the throughput of the system and spectrum utilization.